Treatment and Handling of Hydraulic Shock Load of Urea Fertilizer Wastewater in Sequencing Batch Reactor - Budiastuti, Herawati -; Nurazizah, Annisa; Apriyanti, Fitri; Sudarman, Robby; Ramadhani, Laily Isna; Pullammanappalil, Pratap (Jurnal Internasional Penelitian Teknologi Terapan, 2024)
The production process in the urea fertilizer industry produces wastewater with a very high ammonia content, which exceeds the quality standards for fertilizer wastewater. Therefore, it is necessary to treat urea fertilizer wastewater, which has a high ammonia content. One of the technologies that can be used to treat this type of wastewater is the Sequencing Batch Reactor (SBR) technology. The SBR technology was chosen because it only requires one reactor for the entire process, in which in conventional activated sludge systems it occurs in several reactors. Shock loading often occurs in wastewater treatment plants, including both organic shock loads and hydraulic shock loads. The waste used in the SBR operation in this research is urea fertilizer wastewater originating from a urea fertilizer industry in West Java, Indonesia. The parameters to be tested were COD, MLVSS, DO, pH, temperature, turbidity, and ammonia concentration. The results showed that the efficiency of reducing ammonia levels under normal loading with a flow rate of 300 mL/day was 99.5%, whereas when given a shock load of 600 mL/day, an efficiency of 98% was obtained. This proves that SBR can handle shock loads even though its efficiency slightly decreases.